Differentiation of the human liver progenitor cell line (HepaRG) on a microfluidic‐based biochip. (22nd February 2019) - Jang, Mi; Kleber, Astrid; Ruckelshausen, Thomas; Betzholz, Ralf; Manz, Andreas
Abstract: HepaRG is a bipotent stem cell line that can be differentiated towards hepatocyte‐like and biliary‐like cells. The entire cultivation process requires 1 month and relies on the addition of 2% dimethyl sulfoxide (DMSO) to the culture. Our motivation in this research is to differentiate HepaRG cells (progenitor cells and undifferentiated cells) towards hepatocyte‐like cells by minimizing the cultivation time and without using DMSO treatment by instead using a microfluidic device combined with the following strategies: (a) comparison of extracellular matrices (matrigel and collagen I), (b) types of flow (one or both sides), and (c) effects of DMSO. Our results demonstrate that matrigel promotes the differentiation of progenitor cells towards hepatocytes and biliary‐like cells. Moreover, the frequent formation of HepaRG cell clusters was observed by a supply of both sides of flow, and the cell viability and liver specific functions were influenced by DMSO. Finally, differentiated HepaRG progenitor cells cultured in a microfluidic device for 14 days without DMSO treatment yielded 70% of hepatocyte‐like cells with a highly polarized organization that reacted to stimulation with IL‐6 to produce C‐reactive protein (CRP). This culture model has high potential for investigating cell differentiation and liver pathophysiology research.